2014
DOI: 10.1002/jso.23837
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of anastomotic complications on the health‐related quality of life after esophagectomy

Abstract: Postoperative HRQL is restored within 6 months after discharge. Occurrence of anastomotic stricture significantly decreases HRQL after esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 21 publications
2
21
0
3
Order By: Relevance
“…A prospective cohort study demonstrated that patients who developed an anastomotic stricture after esophageal resection had significantly poorer scores of global quality of life and social function at six months after discharge in comparison with patients without anastomotic strictures [9]. So dilation up to >16 mm may result in a more rapid recovery of the quality of life to a level that is comparable with patients without anastomotic strictures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study demonstrated that patients who developed an anastomotic stricture after esophageal resection had significantly poorer scores of global quality of life and social function at six months after discharge in comparison with patients without anastomotic strictures [9]. So dilation up to >16 mm may result in a more rapid recovery of the quality of life to a level that is comparable with patients without anastomotic strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal strictures cause complaints of dysphagia and weight loss, are associated with a decreased quality of life and lead to additional health care costs [9]. Endoscopic bougie or balloon dilation is currently the standard treatment to resolve dysphagia caused by benign esophageal strictures [10].…”
mentioning
confidence: 99%
“…The change in tongue pressure was not related to anastomotic leakage. The anastomotic leakage and the laryngectomy for cervical esophageal cancer are risk factors for swallowing function [29,30]. In this study, the severe cases of anastomotic leakage were excluded because they received swallowing rehabilitation and reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors were staged according to the 7th edition of the AJCC staging system[ 11 ]. The Mckeown-type procedure was described previously[ 10 , 12 ]: first involved esophageal mobilization and radical mediastinal lymphadectomy through right thoracotomy or thoracoscopy, and then laparotomy or laparoscopic gastric mobilization. A gastric tube is fashioned with a width of approximately 4–5 cm, and pulled through retrosternal or posterior mediastinal routes to the left neck.…”
Section: Population and Methodsmentioning
confidence: 99%
“…Pulmonary complications and anastomotic leakage are the most common serious morbidities, and are great challenges to surgeons, even in experienced centers [ 8 ]. Major complications contribute to substantial perioperative mortality, and dramatically deteriorate quality of life[ 9 , 10 ]. The importance of minimizing the risk of surgical complications can never be overstated.…”
Section: Introductionmentioning
confidence: 99%